Model Komunikasi Konvergensi untuk Perubahan Sosial: Studi Interaksi Warga Kampung dan Kampus UINSA - Suhartini, Rr. (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2017)
The institutional transformation of the State Islamic Institute (IAIN) into the State Islamic University of Sunan Ampel (UINSA) Surabaya has generated on social mobility, horizontal mobility in particular, and has changed the communication patterns of the campus community and villagers. This study discusses the sociology of communications of campus community and citizens of Jemur Wonosari post-transformation of UINSA. It has revealed that the villagers tend to perceive the students as the economic symbol rather than as the agent of change. Students have not contributed to socio-cultural and religious development. Therefore, they need to develop self-concept and perception as change agent and contribute to socio-religious change, especially by using convergence model of communication.